2018
DOI: 10.1111/1440-1703.1008
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure of Asian snakehead fish (Channa striata) in North Borneo: Implications for conservation of local freshwater biodiversity

Abstract: This study quantified the intra‐specific diversity and characterized the population structure of the Asian snakehead fish, Channa striata in Sabah, North Borneo by determining the variability at six microsatellite loci. Range of genetic diversity across all sampled populations was comparatively moderate in relation to levels reported for C. striata populations occurring elsewhere and the overall Sabah population is highly structured, reflecting isolations across geological and ecological time scales. Two recip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 75 publications
(94 reference statements)
2
7
0
Order By: Relevance
“…This finding supports the studies of other taxa that proposed the mountain ranges in Sabah play a role in the maintenance of ancient lineages and species diversity [69,70]. In this study, Labuk River appeared to have potentially retained large proportions of ancestral genotypes as shown by its location in the basal position of the phylogeographic tree, the same results obtained for Channa striata [13]. This shows Sandakan is the origin of colonization before the expansion of populations to eastern clades.…”
Section: Genetic Diversity and Demographysupporting
confidence: 90%
See 3 more Smart Citations
“…This finding supports the studies of other taxa that proposed the mountain ranges in Sabah play a role in the maintenance of ancient lineages and species diversity [69,70]. In this study, Labuk River appeared to have potentially retained large proportions of ancestral genotypes as shown by its location in the basal position of the phylogeographic tree, the same results obtained for Channa striata [13]. This shows Sandakan is the origin of colonization before the expansion of populations to eastern clades.…”
Section: Genetic Diversity and Demographysupporting
confidence: 90%
“…The clustering coincides with the separation of Sabah in the center by CTR and in accordance with major river systems. The results of this study were also obtained by the authors of [13], where Channa striata is subdivided into two genodeme, namely Genodeme 1 and Genodeme 2, which were known in this study as western and eastern clusters, respectively.…”
Section: Phylogeography and Population Structuresupporting
confidence: 70%
See 2 more Smart Citations
“…However, those species also make a different sub-clusters within species, for instance, sample of this study were in different sub-clusters from Indonesia (West and Central Kalimantan), USA (bv=96) and also another sub-clusters of Vietnam, China, the Philippines, Brunei Darussalam, Thailand, and Malaysia (bv=89). Robert et al (2018) reported there were two reciprocally monophyletic genomes of C. striata were identified along the west and east coast that may have been separated by mountain upthrusts throughout the central region of Sabah, Malaysia.…”
Section: Phylogeneticsmentioning
confidence: 99%